Momordica charantia Exosome-Like Nanoparticles Exert Neuroprotective Effects Against Ischemic Brain Injury via Inhibiting Matrix Metalloproteinase 9 and Activating the AKT/GSK3β Signaling Pathway - Cai, Heng; Huang, Lin-Yan; Hong, Rui; Song, Jin-Xiu; Guo, Xin-Jian; Zhou, Wei; Hu, Zhao-Li; Wang, Wan; Wang, Yan-Ling; Shen, Jian-Gang; Qi, Su-Hua (Frontiers in Pharmacology, 2022)
Plant exosome-like nanoparticles (ELNs) have shown great potential in treating tumor and inflammatory diseases, but the neuroprotective effect of plant ELNs remains unknown. In the present study, we isolated and characterized novel ELNs from Momordica charantia (MC) and investigated their neuroprotective effects against cerebral ischemia-reperfusion injury. In the present study, MC-ELNs were isolated by ultracentrifugation and characterized. Male Sprague–Dawley rats were subjected to middle cerebral artery occlusion (MCAO) and MC-ELN injection intravenously. The integrity of the blood–brain barrier (BBB) was examined by Evans blue staining and with the expression of matrix metalloproteinase 9 (MMP-9), claudin-5, and ZO-1. Neuronal apoptosis was evaluated by TUNEL and the expression of apoptotic proteins including Bcl2, Bax, and cleaved caspase 3. The major discoveries include: 1) Dil-labeled MC-ELNs were identified in the infarct area; 2) MC-ELN treatment significantly ameliorated BBB disruption, decreased infarct sizes, and reduced neurological deficit scores; 3) MC-ELN treatment obviously downregulated the expression of MMP-9 and upregulated the expression of ZO-1 and claudin-5. Small RNA-sequencing revealed that MC-ELN-derived miRNA5266 reduced MMP-9 expression. Furthermore, MC-ELN treatment significantly upregulated the AKT/GSK3β signaling pathway and attenuated neuronal apoptosis in HT22 cells. Taken together, these findings indicate that MC-ELNs attenuate ischemia-reperfusion–induced damage to the BBB and inhibit neuronal apoptosis probably via the upregulation of the AKT/GSK3β signaling pathway.